1992
DOI: 10.1063/1.463038
|View full text |Cite
|
Sign up to set email alerts
|

High resolution spectroscopy of 1,2-difluoroethane in a molecular beam: A case study of vibrational mode-coupling

Abstract: The high resolution infrared spectrum of 1,2-difluoroethane (DFE) in a molecular beam has been obtained over the 2978-2996 cm-1 spectral region. This region corresponds to the symmetric combination of asymmetric C-H stretches in DFE. Observed rotational fine structure indicates that this C-H stretch is undergoing vibrational mode coupling to a single dark mode. The dark mode is split by approximately 19 cm -1 due to tunneling between the two identical gauche conformers. The mechanism of the coupling is largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…This fact has motivated the direct study of the intramolecular couplings in these systems using the techniques of high-resolution infrared molecular-beam spectroscopy (3)(4)(5)(6)(7)(8)(9). Philips and coworkers (3)(4)(5)(6) examined the molecular-beam infrared spectra of a series of fluorinated ethanes, 2-fluoroethanol (3), 1,2-difluoroethane (4, 5), 1-chloro,2-fluoroethane (6), and 1,1,2-trifluoroethane (5), to examine the role of steric and electrostatic interactions on their vibrational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This fact has motivated the direct study of the intramolecular couplings in these systems using the techniques of high-resolution infrared molecular-beam spectroscopy (3)(4)(5)(6)(7)(8)(9). Philips and coworkers (3)(4)(5)(6) examined the molecular-beam infrared spectra of a series of fluorinated ethanes, 2-fluoroethanol (3), 1,2-difluoroethane (4, 5), 1-chloro,2-fluoroethane (6), and 1,1,2-trifluoroethane (5), to examine the role of steric and electrostatic interactions on their vibrational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In most previous work, the low frequenc;', large amplitude motion involved torsional motion.s, 6 ,10l,1,1 4 .1s In our previous work on substituted ethanes, we suggested that intramolecular interactions that effect torsional modes, can enhance mode coupling between states involving those torsional modes. 5 ,6, 14 , 15 As noted above, one can view ring puckering in cyclobutane as an extremely hindered torsion, in which the barrier to internal rotation about any C-C bond is essentiai.,. respectively, the K structure is resolved and the weak intensities of these bands prevent us from identifying peak fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…The observed trend in a series of substituted ethanes14, 15 , suggests that the strength of intramolecular interactions correlates with the extent of vibrational mode coupling. Cyclobutane, in a sense, offers an extreme case of intramolecular interaction, in which the C-C torsion is restricted by an additional C-C covalent bond.…”
mentioning
confidence: 96%
“…Another study [93] by Gambogi et al examines the possibility of long range resonant vibrational energy exchange between equivalent CH-stretches in CH 3 Si(C≡CH) 3 . There have been several experiments [94,95,96,97,98] The interpretation of the above experimental results as due to dynamical tunneling is motivated by the theoretical analysis by Stuchebrukhov and Marcus in a landmark paper [103]. In the initial work they explained the narrow features, observed in the experiments [91] by Kerstel et al, by invoking the coupling of the bright states with highly off-resonant gateway states which, in turn, couple back to states that are nearly isoenergetic with the bright state.…”
Section: Connections To Dynamical Tunnelingmentioning
confidence: 99%